99.1k views
5 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation.

6x − y = 1
4x − 3y = −11
Select one:
a. 4(−6x + 1) − 3y = −11
b. 4(6x + 1) − 3y = −11
c. 4x − 3(6x − 1) = −11
d. 4x − 3(−6x − 1) = −11

1 Answer

5 votes

Answer:

6x − y = 1 -------(1)

4x − 3y = −11 ------(2)

(1)×3

18x - 3y =3 ------(3)

4x − 3y = −11 ------(2)

(3)+(2)

18x - 3y + ( 4x - 3y) = 3+(-11)

d. 4x − 3(−6x − 1) = −11 is the answer.

User David Schwartz
by
6.0k points